A guide to field instrumentation in geotechnics principles, installation and reading - Bassett, Richard 1938- (Spon Press, 2012)
This book is written for senior designers, consulting engineers, and major contractors who need a major introduction to the general purpose, availability, and analysis of field instruments before details of their own project can be progressed, and it serves as a textbook to any specialist geotechnical MSc or professional seminar course in which instrumentation forms a major part.